Comparison of high-pressure liquid chromatography and microbiological assay for the determination of biliary elimination of ciprofloxacin in humans. - Brogard, J M (1985)
Serum kinetics and biliary, urinary, and fecal elimination of ciprofloxacin, a new quinolone derivative, were studied in 12 recently cholecystectomized patients provided with T-tube drainage during 24 h after oral administration of a single 500-mg dose of this substance. Drug concentrations were measured by both high-pressure liquid chromatography (HPLC) and microbiological assay. The results were comparable for the concentrations in serum (average of peaks, 2.0 +/- 0.2 micrograms/ml by HPLC and 2.3 +/- 0.3 micrograms/ml by the microbiological method) and urine (0 to 6 h, 267 +/- 74 and 241 +/- 58 micrograms/ml, respectively). This was not the case for biliary values, for which the microbiological assay yielded significantly higher concentrations than did HPLC (average of peak concentrations, 21.2 +/- 2.6 and 16.0 +/- 2.5 micrograms/ml, respectively [P less than 0.02]), nor for total 24-h biliary output (2,167 +/- 288 and 1,587 +/- 222 micrograms, respectively [P less than 0.01]). This suggests hepatic biotransformation of ciprofloxacin into microbiologically active metabolites. The apparent broad antibacterial spectrum of ciprofloxacin and its higher biliary levels than simultaneously determined serum concentrations suggest that this derivative is suitable for the treatment of biliary tract infections.